Endoscopic and histological findings in teats of dairy goats - KIOSSIS (Ε. ΚΙΟΣΣΗΣ) E.; BROZOS (Χ.Ν. ΜΠΡΟΖΟΣ) C. N.; PAPAIOANNOU (Ν. ΠΑΠΑΪΩΑΝΝΟΥ) N.; TZANIDAKIS (Ν. ΤΖΑΝΙΔΑΚΗΣ) N.; BOSKOS (Κ. ΜΠΟΣΚΟΣ) C. (Journal of the Hellenic Veterinary Medical Society, 2017)
Objective of the study was to study the endoscopic examination of teats of dairy goats and to explore the nature and the prevalence of lesions therein. Potentially abnormal findings were further investigated with histological examination. The study was performed in 510 teats from dairy goats, which were collected from slaughterhouses. The endoscopic findings were correlated with those of the histological examination. Of the total teats examined, 16% (82/510) had abnormal findings at the area of teat cistern. The most common finding (66 teats) wast hickness and nodular proliferation of the teat cistern. Diaphragms at the teat cistern were also common (19 teats), while cysts and abnormal findings located at the area of teat cistern were noticed only in 5 and 4 teats, respectively. Variations in the colour of the mucosa of the teat cistern were noticed in 29 cases; in 7 cases teat cistern mucosa was red, in 14 yellow and in 8 red and yellow. Endoscopic examination appears to be an effective technique that might potentially allow evaluation of teat abnormalities in living dairy goats.